2003
DOI: 10.1021/jp036513k
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Two-Photon Absorption Properties for Organic Chromophores Using Time-Dependent Density-Functional Theory

Abstract: In this benchmark study, time-dependent density-functional theory (TDDFT) is applied to calculate one-and two-photon absorption spectra (related to linear and third-order optical responses, respectively) in a series of large donor-acceptor substituted conjugated molecules. Calculated excitation energies corresponding to oneand two-photon-absorption maxima are found to be in excellent agreement with experiment. The evaluated two-photon-absorption cross sections agree with experimental data as well. We conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
210
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(221 citation statements)
references
References 68 publications
11
210
0
Order By: Relevance
“…88 For ground state geometries, we previously found that the Hartree-Fock (HF) method is superior to the DFT-based approaches by reproducing accurately bond length alternation parameters in similar conjugated systems when compared to experiment. 63,89 Moreover, excited state geometry optimizations 90,91 of substituted chromophores may fail due to long-range charge-transfer problems present in DFT. [92][93][94][95] Thus, all ground state geometries are obtained at the HF level using the 6-31G basis set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…88 For ground state geometries, we previously found that the Hartree-Fock (HF) method is superior to the DFT-based approaches by reproducing accurately bond length alternation parameters in similar conjugated systems when compared to experiment. 63,89 Moreover, excited state geometry optimizations 90,91 of substituted chromophores may fail due to long-range charge-transfer problems present in DFT. [92][93][94][95] Thus, all ground state geometries are obtained at the HF level using the 6-31G basis set.…”
Section: Methodsmentioning
confidence: 99%
“…This method has already demonstrated its accuracy (within a factor of 6) for both linear and nonlinear absorption spectra in different series of substituted chromophores. 57,63,89,100 Excited state electronic structures, with 20 excited states for compounds 1-3 and up to 54 for compound 4, were calculated with Gaussian 98 and 03, respectively. 88 Vertical transition frequencies (Ω gν ), dipoles (µ gν ), and densities ( gν ) are used to model both linear absorption and TPA spectra.…”
Section: Methodsmentioning
confidence: 99%
“…We use the B3LYP functional combined with the 6-31G basis set as implemented in the Gaussian 98 package [27]. The 6-31G basis set is known to be an efficient blend of accuracy and manageable size for large conjugated molecules [29].…”
Section: Computational Methodologymentioning
confidence: 99%
“…The SV and similar 6-31G basis sets are known to be an efficient blend of accuracy and manageable size for large conjugated molecules. 48 For the thiophenes and chlorophyll calculations we used geometries extracted from the experimental X-ray crystallographic data. 49,50 In addition to the single molecule limit, we consider thiophene dimers (2Th4) generated from the coordinates of two nearest neighbor pairs in the unit cell.…”
Section: Introductionmentioning
confidence: 99%